Ampliación del Canal de Panamá: Una oportunidad para el comercio exterior en Colombia. (2013)
The present article aims to show the boom that has had foreign trade in recent years with the exchange of goods from one country to another and trade agreements that have been generated, so it has become very important shipping. The Republic of Panama as a country strategically located between the two Atlantic and Pacific Oceans, it has also been developed such as the Panama Canal expansion which will bring benefits not only his own country but also help countries like Colombia which benefit from this great project